Prevalence of mental health conditions among people living with HIV during the COVID-19 pandemic: A rapid systematic review and meta-analysis - Lee, Kai Wei; Ang, Chin Siang; Lim, Sin How; Siau, Ching Sin; Ong, Derek Lai Teik *; Ching, Siew Mooi *; Ooi, Pei Boon * (John Wiley and Sons Inc, 2022)
Background: The COVID-19 pandemic has generated many mental health problems worldwide. People living with HIV (henceforth known as PLHIV) bear a higher mental health burden in comparison with the general population. Therefore, their risk of mental health problems may be elevated during the pandemic. Methods: We conducted a systematic review and meta-analysis to assess the prevalence of depression, anxiety, psychological stress, insomnia and loneliness among PLHIV during the COVID-19 pandemic. Observational studies in four databases published from 1 January 2020 to 30 April 2021 investigating the prevalence of mental health conditions during the COVID-19 pandemic were searched, and 197 articles were retrieved. After the processes of duplication removal, eligibility screening and full-text assessment, 10 articles were included in the systematic review and six articles for meta-analyses. A random-effects model was applied to derive the pooled prevalence of mental health conditions. The risk of bias was assessed using the STROBE checklist. Results: Overall, the pooled prevalence rates of (moderate-to-severe) depression and anxiety among PLHIV were 16.9% [95% confidence interval (CI): 3.8%–30.0%] and 23.0% (95% CI: 12.0%–34.0%), respectively. Conclusions: More research is needed to investigate the mechanism by which the pandemic affects the mental health of PLHIV. Support and programmes are needed to ameliorate the mental health problems in this marginalized population. © 2022 British HIV Association